Innovative Radiating Systems for Train Localization in Interference Conditions - C. Vegni; M. Tosti; A. M. Vegni (International Journal of Antennas and Propagation)
The design of innovative radiating systems based on the metamaterial technology for GNSS (Global Navigation Satellite System) applications in radio frequency (RF) interference conditions is proposed. To this aim, firstly two typical adaptive array techniques (i.e., nulling and beam-forming) are discussed and tradeed off. Secondly, FRPA (Fixed Radiation Pattern Antenna) and CRPA (Controlled Radiation Pattern Antenna) phased array configurations of miniaturized patch antennas are studied by means of electromagnetic commercial tools and phased array optimization algorithms. This process leads to the identification of a phased array design. Benefits and drawbacks for GNSS applications are highlighted. Finally, the design of the phased array is applied to a GNSS user receiver in a navigation realistic environment. Simulation results are obtained in a realistic scenario for railway applications, comprising of a GNSS satellite constellation, a GNSS user receiver (i.e., on-board train equipment) running along a track in Western Australia, and a constellation of interfering satellites. Navigation service performances (i.e., user location accuracy and service availability) are computed taking into account the adaptive array radiation pattern in two different modes (i.e., FRPA or CRPA) and band-limited white noise interference.